A general metric for the magnitude of observer metamerism. (12th September 2014) - Sluban, Boris; Peyvandi, Shahram; Charmchi Avval, Shirin; Amirshahi, Seyed Hossein
<x xml:space="preserve">Abstract</x> Observer metamerism is defined as a property of a pair of spectrally different stimuli having the same colour sensation for an individual (reference) observer. Frequently, samples in this pair no longer match if the observer is changed. In this article, a linear approximation formula is developed that predicts a metameric effect caused by small changes in the observer's colour‐matching functions. This approximation formula enables a general metric of observer metamerism, the observer metamerism potential, to be defined that is independent of any particular deviated observer but still provides a close link to 'observer‐metameric' colour difference. Numerical experiments were conducted to investigate the correlation between the observer metamerism potential and the maximum of 53 metameric colour differences caused by the change from the colour‐matching functions of CIE standard 10° observer to the colour‐matching functions of 49 Stiles and Burch's real 10° test observers. The proposed general metric, together with a previous metric proposed by the present authors, the illuminant metamerism potential, could be taken as a quantitative measure of the performance of spectral approximation methods.